2014
DOI: 10.1590/s0102-86502014000100003
|View full text |Cite
|
Sign up to set email alerts
|

The testis of the mice C57/BL6 offspring in adulthood have alterations due to maternal caffeine consumption

Abstract: PURPOSE:To investigate the effects of the maternal caffeine consumption during pregnancy to adult male testis mice offspring. METHODS:Twenty pregnant mice were divided into control group (c) and caffeine group (cf). dams received daily saline or 20 mg/kg of caffeine subcutaneously. Male offspring were monitored daily until 13 th week. The testis were used to evaluate both the proliferation (pcna) and apoptosis (bax); leptin receptor (ob-r); aromatase; follicle stimulating hormone (fshr), luteinizing hormone (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In the paracetamol group, results showed very few positive cells to PCNA, while there was mild improvement in groups of paracetamol administered curcumin observed by increased number of positive cells but still fewer than control group. These findings were also in agreement with [38] who found decreased positive reaction which was indicating lowered proliferation (measured by PCNA) and an increased apoptosis in the seminiferous tubule. These findings were proved by statistic results of number of PCNA positive cells in different groups as there were significant decrease among treated group.…”
Section: Discussionsupporting
confidence: 92%
“…In the paracetamol group, results showed very few positive cells to PCNA, while there was mild improvement in groups of paracetamol administered curcumin observed by increased number of positive cells but still fewer than control group. These findings were also in agreement with [38] who found decreased positive reaction which was indicating lowered proliferation (measured by PCNA) and an increased apoptosis in the seminiferous tubule. These findings were proved by statistic results of number of PCNA positive cells in different groups as there were significant decrease among treated group.…”
Section: Discussionsupporting
confidence: 92%
“…They observed significant dose-related decreases in the body (11.09%) and testis weight (22.56%) of male offspring rats, at low and high dose caffeine-fed animals, respectively. Also Cavalcant et al [27] reported that maternal caffeine administration during pregnancy causes a significant reduction in food intake and the body mass gain of the offspring. In addition, caffeine-fed animals consumed less food on average than the control group and there seemed to be a causal relationship between food consumption and body weight.…”
Section: Discussionmentioning
confidence: 99%
“…66,68 Some female-specific features of leptin and VEGF relation in obesity were also revealed: downregulated VEGF and HIF-1A synthesis and leptin level in fat tissue in response to estrogen in rats 88 ; increased VEGF expression in uterine tissue in response to estrogen and leptin in conditions of HF diet 89 in mice; attenuated values of VEGF and leptin in fetal serum and decreases testicular VEGF level in offspring in response to caffeine in pregnant mice. 91 This emphasizes the need for genderspecific investigations of leptin-VEGF crosstalk. Genetic inquiries confirmed the two-directional relationship between leptin and VEGF in obesity and related disorders, suggesting a genetic basis of this bidirectionality and its involvement in adipose tissue browning.…”
Section: Discussionmentioning
confidence: 99%
“…89 In pregnant animals, caffeine attenuates the values of VEGF and leptin in fetal serum and decreases testicular VEGF leve in offspringl. 91 This narrow but important group of results clearly shows that leptin-VEGF crosstalk may be gender-specific. This aspect of the interactions between leptin and VEGF has never before been investigated and urgently needs research attention, as it may at least partially be a basis for differences between female and male obesity.…”
Section: Animal Studiesmentioning
confidence: 98%
See 1 more Smart Citation